EFFECTIVENESS OF FOOTBALL TRAINING ON THE MOTOR ABILITIES OF 12-YEAR OLD STUDENTS - D. Nancheva; D. Ivanov (Trakia Journal of Sciences)
The issue of developing the motor abilities of students is highly relevant to school-based physical education. Few specialists plan the development of motor qualities in relation to the formation of motor skills, and this is particularly true in football lessons. In this regard, we conducted a study aimed at determining the effectiveness of football training on the motor abilities of 12-year-old students. To achieve this, we conducted a one-time testing at the end of the 2023/2024 academic year involving 70 sixth-grade students (from "Victor Hugo" Secondary School No. 81 in Sofia -EG, and "Hristo Yasenov" Secondary School in Etropole -CG). Methods: The experimental group (EG) followed a thematic plan that included lessons for targeted football training. The control group (CG) followed a standard methodology where lessons did not emphasize the development of specific football skills. The study was conducted using the following tests: 10 m sprint, 20 m sprint, agility test, dribbling, standing long jump with both feet, shuttle run 6x20, and juggling.Results: After processing the results, we found significant differences in the motor abilities of the students in the experimental group compared to the control group. The experimental group showed improved motor skills and habits that meet the learning outcomes for football training, as well as developed motor qualities associated with their specific physical manifestations. Conclusion: Conducting football training during physical education classes contributes to meeting the requirements for the implementation of the educational content and provides better opportunities for improvement in this specific sport.